Réponses

2014-03-03T14:57:11+01:00
F 144 - x² = 0         12² - x² = 0   (12-x ) ( 12 + x ) = 0   12-x = 0 ou 12+ x = 0 Donc x = 12 ou x = -12                                                                                                           G 49 - 70x + 25x²   =     7² - 2 x 7 x 5  x + (5x)² =  0                                                                                         (7-5x )²  = 0   donc 7-5x = 0  alors -5x = 7  x = -7/5                    H       13x² - 4y² =    0     (13x-4y)   (13x+4y) = 0        13 x - 4y = 0  ou 13x+4y = 0        26 x = 0    x = 0  et y également = 0                                                                            I      (x+ 2 )² - ( 3x+5)²    x² + 2 x 2x + 4  - ( 9x² + 2 x 3x X 5 ) + 5² )    = x² + 4x + 4 - 9x²  - 30x  - 25 = -8x² - 26x - 21